Meeting of the Consultative Committee of Parliament for the Ministry of Planning and Programme Implementation - Planning Commission (Planning Commission, 1989)
On September 18, 1989, a meeting of the Consultative Committee of Parliament for the Ministry of Planning and Programme Implementation focused on "Environmentally Sustainable Development." The discussions highlighted the necessity for sustainable development, emphasizing that it must meet present needs without compromising future generations. Key strategies included increasing productivity, conserving resources, and improving the quality of life. Pollution control, particularly in air and water, emerged as a significant concern, necessitating integrated planning and public awareness. The meeting stressed the importance of education, research, and community involvement in achieving ecological and livelihood security while maintaining economic efficiency and social equity. Urgent action points for the upcoming decade were also identified, aimed at fostering ecological integrity and implementing stricter environmental policies.
Environmentally Sustainable Development
Ministry of Planning and Programme Implementation
Keywords: Sustainable Development; Pollution Control; Resource Management; Community Involvement; Policy Framework; Sustainable Development Defined